Warm compresses to decrease dysmenorrhea among adolescents - Dian Nurafifah; Ihda Mauliyah; Atiul Impartina (Journal of Health Technology Assessment in Midwifery, 2020)
Dysmenorrhea is one of discomfort experienced by adolescent during menstruation. A Survey of 10 young women at University of Muhammadiyah Lamongan found 90% had dysmenorrhea. To reduce pain, they take pain relievers. However, the use of drugs can cause side effects, especially if long-term use can lead to addiction or dependence. Research design using Quasy Eksperiment (pretest-posttest). The study was conducted on adolescents who are experiencing dysmenorrhea. They were divided into two groups namely control and treament groups. The study began by assessing pain levels in both groups. The treatment group was given warm compresses but the control group was not given any treatment, after that reassess the level of pain. The study analyzes changes in pain levels and compares pain change in the two groups. The results showed that in the control group most of the adolescents did not experience pain changes during dysmenorrhea (86.7%), whereas in the treatment group most of the adolescents experienced a decrease in pain (93.3%). Data analysis using the Mann Whitney test showed p=0.000 where p0.05 so it can be concluded that there are differences in dysmenorrhea before and after treatment between the warm compress group and the control group. The results of this study are expected to be used as consideration in developing plans to reduce discomfort in the form of menstrual pain in a non-pharmacological manner.